RAGE gene polymorphism (rs1800625) and type 1 diabetes mellitus: A potential new model for early diagnosis and risk prediction - Mohamed, Amal A.; Al-Obeidat, Feras; Abdallah, Gamil M.; Ibrahim, Ibrahim T.; Ali, Nada S.; Hussein, Mona A.; Hafez, Wael; Girgiss, Mina W.; Shalby, Hassan; EL-Bohy, Doaa; Elgamal, Rasha; Farghly, Maysa I.; Shaheen, Mahmoud M.; Elmahdy, Reem; Nagaty, Raghda A.; Hassan, Noheir AIF.; Hamdi, Amel; Mahmoud , Mohamed O. (Narra Sains Indonesia, 2025)
Studies have associated advanced glycation end-products (AGEs) and the polymorphism of the AGEs receptor (RAGE) gene with clinical disorders, such as diabetes, in certain ethnic groups. However, its association with type 1 diabetes mellitus (T1DM) in Egyptians has not yet been explored. The aim of this study was to investigate the association between the RAGE gene polymorphism rs1800625 and T1DM susceptibility in Egyptians. A case-control study was conducted with 177 T1DM patients and 177 age- and sex-matched healthy controls. Variables included glycemic markers (fasting blood glucose (FBG), postprandial blood glucose (PBG), hemoglobin A1c (HbA1c)), anthropometric measurements (waist circumference, body mass index (BMI)), lipid profile (total cholesterol, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL)), renal function (albumin-to-creatinine ratio (A/C ratio), serum creatinine), and history of hypertension and smoking. Genotype distribution and allele frequency of the RAGE rs1800625 polymorphism (TT, TC, CC genotypes; T and C alleles) were assessed. This study identified the RAGE rs1800625 polymorphism as a significant genetic factor associated with T1DM susceptibility. The CC genotype was significantly more prevalent in patients compared to controls (29.9% vs 11.9%; OR: 3.62; 95%CI: 1.87–6.97; p<0.001). Similarly, the C allele was more common in patients (54.5% vs 41.0%, OR: 1.73; 95%CI: 1.28–2.33; p<0.001). Multivariate analysis revealed that HbA1c (adjusted OR (aOR): 12.97; 95%CI: 4.00–42.05; p<0.001), FBG (aOR: 8.96; 95%CI: 1.59–50.47; p=0.010), and the rs1800625 polymorphism (aOR: 1.82; 95%CI: 1.146–2.876, p=0.010) were significant predictors of T1DM. In conclusion, a genetic association was found between the RAGE gene polymorphism rs1800625 and T1DM susceptibility, with the CC genotype and C allele being more common in T1DM patients. FBG, HbA1c, and rs1800625 were identified as key predictors for T1DM, with HbA1c being the strongest. These findings highlight the importance of integrating genetic and metabolic factors in managing T1DM.